CONSTRAINTS THAT AFFECT THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT ON EXECUTIVE MANAGEMENT AND EFFECTIVENESS OF PLANNING IN THE ORGANIZATION AS A MEDIATOR - Sami Abdullah Kadhim; Saad Faysil Mahmoud (Scholar Express Journals, 2024)
Total Quality Management (TQM) is an activity that helps develop the organization on an ongoing basis on affects Executive Management (EM) through highly efficient Planning (PL) as a mediator. Total quality management is capable of improving organizations in different ways. By analysing the results of the targeted sample and determining the discussion in this study, the researcher was able to determine the impact of total quality management on executive management, and role planning as a mediator has clearly contributed through continuous improvement. The impact of total quality management on executive management is evident by supporting organizations with modern, high-tech plans to contribute to community satisfaction. Quality is characterized by the organization's high performance in production and leads to improving workers' lives, provided that this is accompanied by successful management. This study focuses on the type of modern methods that are well used in performance, and then constantly monitors and searches for problems to which the organization is exposed. The researcher relies on accuracy in analyzing the results in a clear manner to reach the desired results. The target sample number was (158), he was wrong (6), and true questionnaire (152). Statistical analysis was used SPSS & SmarrtPLS 4, and used Likert scale 7, target sample was Wasit University/Iraq
Keywords: Total quality management; executive management; planning; organizations